Effect of 30 day tamponade using perfluorocarbon liquid on the bioelectric functional activity and structure of the rabbit's retina (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The use of perfluorocarbon liquid (PFCL) for short-term tamponade can broaden retinal detachment surgery indications and improve outcomes. However, there is no common opinion regarding the effect of PFCL on the functional state of the retina. It is relevant to compare the effect of PFCL and light silicone oil (SO).Purpose was to study the effect of 30 day PFCL tamponade on bioelectrical functional activity and structure of the retina in rabbits’ eyes and to compare the actions of PFCL, SO (specific gravity
Keywords: retinal structure; functional activity; electroretinography; perfluorocarbon liquid; silicone oil; experiment